Insights into The Adoption of Lean Management in Industrialised Building System (IBS) Implementation: The Drivers and Challenges - Rahimah Mohd Noor, Siti; Yunus, Riduan; Halid Abdullah, Abd; Nagapan, Sasitharan; Mohamad Syahir Syed Mazlan, Syed (International Journal of Engineering and Technology, 2018)
The application of lean management is able to improve construction processes. Unnecessary waiting time, overstaffing and risk uncertainty are some of the problems that can be eliminated by adopting lean management. Industrialised Building System (IBS) is a sustainable approach that can be improved construction deliverables with the integration of lean management. However, the adoption or practice of lean management in productions of IBS component productions is still limited. There are only few studies emphases on the interactions among key drivers and hierarchy of lean management key drivers model. This study used Interpretive Structural Modeling (ISM) to interpret relationship of drivers and challenges in integrating lean management in form of ISM based-model and Matrice dâ€™impacts croisÃ©s multiplication appliquÃ©e an classment (MICMAC). The results from this will improve the adoption of lean management in IBS application.Â Â